Moving Toward a Reader-Centred Classroom: Students’ Reflection on Reading - Rachmawati, Umi; Nisa Syuhda; Santi Andriyani (ETERNAL (English Teaching Journal), 2025)
This study is aimed gathering the students’ reflection on their reading class for the baseline of the development of reflective reading materials. The student-centered classroom implies in the process of developing reading materials that support the students critical thinking and reflective skills. This study was mostly conducted qualitatively though quantitative data were also gathered to strengthen the findings. The study involved a total of 52 students from English Education Department in a reputable university. The focus of the instruments used to include questionnaire and interviews used is to access details of reading materials, reading process, and students’ reflection. The research participants were selected purposively. The results of the study present that the needs of developing reading materials that support the students’ critical and reflective skills are highly required and the considerations of aspects of the students’ reading materials, process of reading class, and reflection on students’ reading will facilitate the development of effective and engaging learning materials.